The Effect of Adding Nutrients to Rice Washing Waste Water on Growth Results of Yellow Soybean Plant Microgreens (Glycine max (L.) Merill) - Ashari, Maya; Rahmadina, Rahmadina; Idami, Zahratul (Jurnal Biologi Tropis, 2024)
Soybeans contain many vitamins and minerals and are low in saturated fatty acids. Food ingredients derived from soybeans are also free from lactose, making them suitable for consumers who suffer from lactose intolerance. It is impossible to separate microgreens growth from their requirement for nutrients and water. Since microgreens are organic, chemical fertilizers are not used to them. Rice washing waste water is one substitute that can be utilized as fertilizer for microgreen plants. The purpose of this study is to ascertain the optimal concentration for maximizing the growth and yield of yellow soybean microgreens (Glycine max) and the impact of giving waste rice washing water on these microgreens. This study conducts quantitative research using an experimental design. A non-factorial randomized block design (RAK) was employed to collect the data, with concentration being the primary variable (P0: Control, P1: 50 ml rice washing water, P2: 100 ml rice washing water, P3: 150 ml rice washing water). Plant height, plant dry weight, plant wet weight, and chlorophyll levels are all significantly impacted by the availability of rice washing water, according to the research findings. The amount of leaves was unaffected by the presence of rice washing water. Plant height, dry weight, wet weight, and chlorophyll content can all be increased with P1 in as much as 50 milliliters of rice washing water.